Physical Activity and Depression and Anxiety Disorders in Australia: A Lifetable Analysis - Mary Njeri Wanjau, MPPM; Holger Möller, PhD; Fiona Haigh, PhD; Andrew Milat, PhD; Rema Hayek, MCom; Peta Lucas, BHMSc; J. Lennert Veerman, PhD (Elsevier, 2023)
Introduction: Mental disorders, in particular, depressive and anxiety disorders, are a leading cause of disability in Australia and globally. Physical activity may reduce the incidence of anxiety and depression, and this supports the inclusion of physical activity in strategies for the prevention of mental ill health. Policy makers need to know the potential impact and cost savings of such strategies. We aimed to quantify the impact of changes in physical activity on the burden of anxiety and depression and healthcare costs in Australia. Methods: We used a proportional multistate lifetable model to estimate the impact of changes in physical activity levels on anxiety and depression burdens for the 2019 Australian population (numbering 24.6 million) over their remaining lifetime. The changes in physical activity were modeled through 3 counterfactual scenarios informed by policy targets: attainment of the Australian Physical Activity Guidelines and achievement of the WHO Global Action Plan on Physical Activity targets of a 10% relative reduction in the prevalence of insufficient physical activity by 2025 and a 15% relative reduction by 2030. Results: If all Australians adhered to the recommended minimum physical activity levels, in 25 years' time, the burden of anxiety could be reduced by up to 6.4% (95% uncertainty intervals=2.5, 10.6), and that of depression could be reduced by 4.4% (95% uncertainty intervals=2.3, 6.5). Over the lifetime of the 2019 Australian population, the gains could add up to 640,592 health-adjusted life years for anxiety (26 health-adjusted life years per 1,000 persons), 523,717 health-adjusted life years for depression (21 health-adjusted life years per 1,000 persons), and healthcare cost savings of 5.4 billion Australian dollars for anxiety (220 Australian dollars per capita) and 5.8 billion for depression (237 Australian dollars per capita). Conclusions: Adherence to the Australian physical activity guidelines and achievement of the 2025 and 2030 global physical activity targets could lead to a substantial reduction of the burden of anxiety and depression. This study provides empirical support for the inclusion of physical activity in strategies for the prevention of mental ill health. Future studies should also assess the size and distribution of the benefits for different socioeconomic and ethnic groups.